A Model for Fair Trade Buying Behaviour: The Role of Perceived Quantity and Quality of Information and of Product-specific Attitudes - De Pelsmacker, Patrick (Journal of business ethics, 2007)
In a sample of 615 Belgians a model for fair trade buying behaviour was developed. The impact of fair trade knowledge, general attitudes towards fair trade, attitudes towards fair trade products, and the perception of the quality and quantity of fair trade information on the reported amount of money spent on fair trade products were assessed. Fair trade knowledge, overall concern and scepticism towards fair trade, and the perception of the perceived quantity and quality of fair trade information, influence buying behaviour directly and indirectly through product attitudes. Interest in fair trade products, price acceptability and product liking have a significant impact on fair trade buying behaviour. Product interest is the most important variable influencing buying behaviour. Implications for the campaigns of governments and for the marketing strategy of fair trade organisations are offered.